2014
DOI: 10.1089/fpd.2014.1770
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofEscherichia coliO157:H7 in Surface Water Near Cattle Feedlots

Abstract: Between April 2009 and July 2011, 311 surface water samples in 48 cattle feedlots distributed in an area of about 67,000 km(2) were analyzed to examine the environmental dissemination of Escherichia coli O157:H7. Samples were taken inside and outside the pens, exposed and not exposed to runoff from corrals, near the feedlots. Two types of samples were defined: (1) exposed surface waters (ESW; n=251), downstream from cattle pens; and (2) nonexposed surface waters (NESW; n=60), upstream from cattle pens. By mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…For example, studies conducted in the European Union have reported use of ISO methods (commonly used ISO 7899-2 method) as per the requirements of European Drinking Water Directive 98/83/EG. These methods use 24-h sample holding time before the analysis of water samples, which is in agreement with the conclusion of this study [23,24]. Moreover, in Australia their drinking water standards are similar to the United States but hold stricter requirements for frequency and level of E. coli levels using AS/NZS 5667.5:1998 which requires samples held less than 24 h [25].…”
Section: Resultssupporting
confidence: 80%
“…For example, studies conducted in the European Union have reported use of ISO methods (commonly used ISO 7899-2 method) as per the requirements of European Drinking Water Directive 98/83/EG. These methods use 24-h sample holding time before the analysis of water samples, which is in agreement with the conclusion of this study [23,24]. Moreover, in Australia their drinking water standards are similar to the United States but hold stricter requirements for frequency and level of E. coli levels using AS/NZS 5667.5:1998 which requires samples held less than 24 h [25].…”
Section: Resultssupporting
confidence: 80%
“…Such diverse stx genotypes in environmental STEC O145 strains may suggest the presence of diverse Shiga toxin-encoding phages in this agricultural environment. Infective Shiga toxin-encoding phages have previously been detected in various ecosystems and in fecal samples from animals and humans (54)(55)(56)(57)(58)(59), and transfer of stx genes has been demonstrated in water and food samples (60). These phages persisted better in nonhost environments than in their bacterial hosts and retained their infectious activities in harsh environments (61,62), implying the potential of stx acquisition by phage transduction in natural environments (63,64).…”
Section: Resultsmentioning
confidence: 99%
“…coli O157:H7 was found in 100 and 1000 mL of private water supply samples 2.7% of private wells [33]. In Argentina, surface water samples in 48 cattle feedlots yielded 70.5% rfb positive and 12.7% STEC in runoff from corrals exposed surface waters and 60.0% rfb positive and 10.0% STEC in non-exposed surface waters sampled as two liters with Moore swabs [34]. In this study, all six genes were detected in different percentages.…”
Section: Discussionmentioning
confidence: 99%